Minutes of General Council (extract)
030-0151-001 Extract from G.C. Minutes 22nd June 38. Item 98. Spain. (d) Trade Union funds. Mr. Lawther explained that the money from the Durham Miners' Association was earmarked for the Asturian Miners' children. The Secretary asked that the money should be sent to Spain through the International Solidarity Fund. 292/946/30/151